PENGARUH KEPEMILIKAN MANAGERIAL, KEPEMILIKAN INSTITUSIONAL, FREE CASH FLOW DAN PROFITABILITAS PADA KEBIJAKAN DIVIDEN - Purnama Sari, Ni Komang Ayu; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The purpose of this study to examine the effect of managerial ownership, possession institusonal, free cash flow and profitability in the dividend policy of testing under investigation in an attempt to go public institution that goes into the manufacturing category and recorded on the stock exchanges of Indonesia from 2010 - 2013. purposive sampling a method used in determining the sample in the study, samples were obtained by 8 companies and to 32 observations. Multiple linear regression analysis is a method used in the study. After the analysis found that the independent variables are the result of managerial ownership and free cash flow have a significant influence on the dividend payout ratio (DPR), as well as institutional ownership and profitability no significant effect on the dividend payout ratio.
Keywords: Managerial Ownership (KM), Institutional Ownership (KI), Free Cash Flow (FCF), Profitability, Dividend Policy.